Penetapan Penerimaan Besaran Pembiayaan pada KPN Syariah dengan Metode AHP - Hasni, Salmi; Nurcahyo, Gunadi Widi; Yunus, Yuhandri (SEULANGA SYSTEM PUBLISHER, 2019)
The financing approval process for the Al-Ikhlas Sharia Civil Servant Cooperative (KPN) of the Batusangkar State Islamic Institute (IAIN) is still carried out by manual review, making it difficult to receive financing quickly and accurately. As a solution to these problems, we need a decision support system that can help in determining the amount of financial revenue. Analytic Hierarchy Process (AHP) is one of the multi-criteria problem solving models used in this study. The criteria used in determining the amount of financing received at the Al-Ikhlas IAIN Sharia Batusangkar KPN are character, capital, capacity, condition, and collateral. This study produces a weighting matrix of results, with KS as the member who gets the highest score of 95.3% and can apply for financing with a maximum amount.